Transforming mature industries into growth industries: the case of US peanuts - Foko, Emmanuel (Kansas State University, 2008)
For more than a decade, the consumption of peanuts as food has been stagnant. This situation has been attributed to several factors. This study seeks to identify and understand some of the factors that have hindered growth in this industry and attempts to present recommendations that will be useful in transforming the peanut industry from stability to growth. We determined that in addition to peanut prices, consumers' income and young children's share of the total population, substitute snack foods such as potatoes chips and popcorn influenced peanut consumption. We also discovered that consumer perception about peanut's fat content and the increasing concern about peanut allergies affected their consumption behavior. The research used data drawn from US Census Bureau, Department of Labor Statistics, National Agricultural Statistics Services, and various industry publications. We suggest that changing the consumption trend lines in the peanut industry can be achieved through effective innovation and focused marketing of the product's health and convenience benefits.
Keywords: Peanuts; Mature Markets; Agricultural Innovations; Entrepreneurship in Agriculture; Agribusiness; Agribusiness Statistical Analysis; Business Administration, Marketing (0338); Economics, Agricultural (0503); Economics, Commerce - Business (0505)